2013
DOI: 10.2224/sbp.2013.41.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Risk-taking and Impulsive Behaviors: a Comparative Assessment of Three Tasks

Abstract: The balloon analogue risk task (BART), the delay discounting task (DDT), and the Iowa gambling task (IGT) are increasingly used for the assessment of risk-taking and impulsive behaviors. This study examined the reliability of and relationships between these three tasks in healthy Chinese subjects. The BART and DDT showed moderate to high test-retest reliability across three test sessions. However, the IGT showed low reliability for the first two sessions but high reliability for the last two sessions. Between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 30 publications
5
49
1
1
Order By: Relevance
“…Xu et al. (2013) suggested that risk-related cognitive processing mediating the BART behavior may be different than the delay discounting. Delay discounting refers to the degree to which the subjective value of a commodity decreases as a function of a delay in its delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al. (2013) suggested that risk-related cognitive processing mediating the BART behavior may be different than the delay discounting. Delay discounting refers to the degree to which the subjective value of a commodity decreases as a function of a delay in its delivery.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to investigate delay discounting among individuals with IGD. Few studies have attempted to compare the performance on the BART, IGT, and Experiential Delay discounting Task (EDT) in IGD (Xu, Korczykowski, Zhu, & Rao, 2013), and the reliability of the trials on these tasks was mixed. Hence, there is a need to compare risk-taking and delay discounting two facets of impulsivity in individuals with IGD.…”
Section: Introductionmentioning
confidence: 99%
“…However, the differences in findings could also be related to differences in decision-making paradigms. Prior comparisons of the BART and IGT (Bornovalova et al, 2009; Mata et al, 2012; Xu et al, 2013) have identified important distinctions between the two measures (e.g., differences in pay-off structures, learning requirements, and amount of ambiguity). It is possible that detection of associations between striatal DA signaling and IGT performance requires provocation of the system.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Moreover, it presents convincing test-retest characteristics [44, 45]. The software The Psychology Experiment Building Language was used for implementation [46, 47].…”
Section: Methodsmentioning
confidence: 99%